2017
DOI: 10.1021/acs.langmuir.7b01937
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Self-Assembled Monolayers Revealed via Inverse Tensiometry

Abstract: Self-assembled monolayers (SAMs) have emerged as a simple platform technology and hence have been broadly studied. With advances in state-of-the-art fabrication and characterization methods, new insights into SAM structure and related properties have been delineated, albeit with some discrepancies and/or incoherencies. Some discrepancies, especially between experimental and theoretical work, are in part due to the misunderstanding of subtle structural features such as phase evolution and SAM quality. Recent wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 107 publications
5
58
1
Order By: Relevance
“…Through the analysis based on Bragg's law, it can be concluded that the long‐chain SAMs have stronger tendency to form ordered hexagonal structures with 3×3R30 symmetry, as compared to the short‐chain ones . Moreover, the evidence from nuclear magnetic resonance (NMR) spectroscopy, sum frequency generation (SFG) studies and molecular dynamics (MD) simulations also suggest that the molecular mobility of long‐chain SAMs is significantly restricted because the strong intermolecular van der Waals attraction reduces the free volume and increases the packing density, and the great lag in the molecular correlation and orientation could also imply the crystalline‐like arrangement of the long‐chain hydrocarbon chains . In addition, surface nanoscale structure and molecular mobility can be tuned within the SAM by coadsorbing two kinds of thiols with different chain lengths ,,.…”
Section: Methodsmentioning
confidence: 99%
“…Through the analysis based on Bragg's law, it can be concluded that the long‐chain SAMs have stronger tendency to form ordered hexagonal structures with 3×3R30 symmetry, as compared to the short‐chain ones . Moreover, the evidence from nuclear magnetic resonance (NMR) spectroscopy, sum frequency generation (SFG) studies and molecular dynamics (MD) simulations also suggest that the molecular mobility of long‐chain SAMs is significantly restricted because the strong intermolecular van der Waals attraction reduces the free volume and increases the packing density, and the great lag in the molecular correlation and orientation could also imply the crystalline‐like arrangement of the long‐chain hydrocarbon chains . In addition, surface nanoscale structure and molecular mobility can be tuned within the SAM by coadsorbing two kinds of thiols with different chain lengths ,,.…”
Section: Methodsmentioning
confidence: 99%
“…The existence of covalent bonds between at the S/L interfaces renders a strong stability of the liquid layers. The covalently bonded liquid layers, which form spontaneously when in contact with TiB 2 and sapphire substrates, are analogous to the layered water [6] near solid substrates and the self-assembled monolayers (SAMs) grown above the metal substrates [53,54]. Hence, the theories in these systems can be borrowed to analyze the liquid metal layering near the nucleant substrates (normally ceramics).…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to explore the factors that might contribute to these differences. The surface roughness of the substrate is a vital factor that greatly influences the behaviors of the nearsurface layering or the self-assembly of atoms (or molecules) [8,53,54]. In this work, we focus on the atomically smooth surfaces, and our results show that when liquid Al is in contact with the atomically smooth surfaces of (0001) sapphire and (0001) TiB2, stratified liquid structures develop spontaneously.…”
Section: Factors Influencing Substrate-induced Liquid Al Layeringmentioning
confidence: 93%
“…We infer that, due to the nature of the carboxyl ligands,shorter chains would tend to pack better on the curved surface due to limited degree of freedom and thus form the most ideal and equally distributed passivating layer. [34] Formic acid (lowest pK a ), however might be too acidic, hence high etching rate that is detrimental towards the integrity of the native oxide and the metal itself,r esulting in significant dealloying (Supporting Information, Figure S14b). Longer chains would also lead to phase transformation into am ore independent system (selfassembled monolayer), [34] thus increasing the interfacial distance and reducing the intensity of the chemical potential gradient and mirror charge within the surface oxide.…”
Section: Angewandte Chemiementioning
confidence: 99%